Dinamika Sosial Budaya dan Transmisi Nilai-Nilai Islam dalam Pendidikan Karakter Anak Usia Dini di Era Digital di RA Muslimat 12 - Faridah Faridah; Aries Munandar (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2026)
The rapid development of digital technology has significantly transformed the socio-cultural dynamics of society, including Islamic-based early childhood education. This article aims to analyze socio-cultural dynamics and the transmission of Islamic values in character education for early childhood in the digital era, using RA Muslimat 12 as a case study. The study is grounded in the phenomenon of increasing digital technology use in family and educational settings, which simultaneously presents opportunities and challenges for character formation. Employing a qualitative approach with a case study design, data were collected through participant observation, in-depth interviews with the head of the institution, teachers, parents, and documentation of learning activities. The findings reveal that socio-cultural dynamics in the digital era influence interaction patterns among children, teachers, and parents in both learning processes and value habituation. The transmission of Islamic values at RA Muslimat 12 is carried out through curriculum integration, teacher role modeling, habituation of religious practices, and the selective and contextual use of digital media. This article emphasizes that Islamic value-based character education for early childhood in the digital era requires strong synergy between educational institutions, families, and the broader social environment, while remaining grounded in humanistic and moderate Islamic pedagogical principles.